111In-Pentetreotide (OctreoScan) scintigraphy in the staging of small-cell lung cancer. Issue 2 (February 2015) - Genestreti, Giovenzio; Bongiovanni, Alberto; Burgio, Marco Angelo; Burgio, Salvatore Luca; Musto, Alessandra; Rossi, Alice; Monti, Manuela; Scarpi, Emanuela; Ulivi, Paola; Bravaccini, Sara; Dubini, Alessandra; Matteucci, Federica; et al.
<x xml:space="preserve">Abstract</x> Background Small-cell lung cancer (SCLC) may express somatostatin transmembrane receptors (SSTRs) in 50–75% of cases. We evaluated the accuracy and prognostic significance of somatostatin receptor scintigraphy (SSRS) in staging compared with conventional radiological procedures. Patients and methods Newly diagnosed SCLC patients underwent scintigraphy with the radiolabeled somatostatin analog indium-111 (111In)-pentetreotide (OctreoScan). Histological data were available for 20 (38%) patients for immunohistochemical analysis of SSTR-2 expression. Results From May 2007 to December 2011 we analyzed 52 SCLC patients. In comparison with standard radiologic staging, the sensitivity and specificity of SSRS were 63 and 100% for primary pulmonary tumor (T), 51 and 100% for mediastinal lymph node (N), and 23 and 91% for metastatic disease (M), respectively. The overall SSRS accuracy was 65% for T, 62% for N, and 52% for M. Patients with positive SSRS achieved a disease control rate of 97 versus 84% in those with negative exam results; median progression-free survival was 9.5 months versus 11.0 and median overall survival was 15.3 versus 14.5 months for patients with positive SSRS versus those with a negative result. Notably, seven (78%) patients with a positive quantitative analysis for SSTR-2 had a positive SSRS; at semiquantitative analysis this correlation was found in eight (73%) patients. Conclusion SSRS has a lower accuracy in comparison with standard radiological staging in SCLC. However, patients with a positive SSRS given standard treatments showed better disease control compared with those with a negative SSRS, but similar progression-free survival and overall survival.